Computer simulation of orthodontic tooth movement using CT image-based voxel finite element models with the level set method. Issue 5 (3rd April 2016) - Hasegawa, Masakazu; Adachi, Taiji; Takano-Yamamoto, Teruko
Abstract : Orthodontic tooth movement (OTM) is an adaptive biomechanical response of dentoalveolar components to orthodontic forces, in which remodeling of the alveolar bone occurs in response to changes in the surrounding mechanical environment. In this study, we developed a framework for OTM simulation by combining an image-based voxel finite element method, with a surface-tracking level set method using three-dimensional computer models. For a case study to demonstrate its capability of expressing clinical tooth movement, we observed displacement and rotation of the tooth under three types of force conditions. The simulation results demonstrate that the proposed simulation method has the potential to predict clinical OTM.